Intracranial CT findings in traumatic brain injury: A retrospective, cross-sectional study among Igbo population in Nigeria - Angel-Mary Anakwue; Felicitas Ugochinyere Idigo; Uloma Benedicta Nwogu; Sylvester Osita Ogbu; Anthony Nnamani; Kennedy Joseph; Camillus Chukwuemeka Ugwoke (Journal of Health and Social Sciences)
Introduction: Traumatic brain injury (TBI) is a major cause of death and disability and in recent years has been increasingly reported even in developing countries. Computed Tomography (CT) plays a key role in accurate TBI diagnosis and management. The objective of this study was to document the pattern of CT findings in TBI cases reported from Igbo people, in Nigeria. Method: In this retrospective, cross-sectional study, a sample of 287 patients, who were consecutively referred to the CT Unit of the Radiology Department of Federal Medical Centre in Umuahia, Nigeria, between January 2015 and December 2016, on account of trauma to the head was reviewed. Only CT scan without contrast and intracranial findings were considered. Descriptive statistics (frequency and percentages) and confidential intervals were collected. Results: After applying exclusion criteria, our sample comprised 242 patients (M = 163, 67.4%; mean age 32.6 ± 17.6 years). The peak age range was 20–29 years. Abnormal findings were reported for 205 patients (84.72%, 95% Confidential Interval [CI] 80.0 to 86.8). Cerebral oedema was the most common finding observed in the study (n = 64, 24.44%, CI 19.03% to 29.85%), followed by subarachnoid haemorrhage (n = 41, 16.94%, CI 12.21% to 21.67%) and epidural haematoma (n = 26, 10.74%, CI 6.84% to 14.64%). Only 37 patients (15.28%) showed normal findings. Main reported causal factors of TBI were: Road Traffic Accidents (RTA) (35.5%), falls (20.2%) and assault (15.7%). Most cases of RTA (34.9%) occurred in the age group of 20–29 years. Discussion and Conclusion: CT brain without contrast is useful in screening of patients with TBI. In this Nigeria-based study the most common cause of TBI was RTA and cerebral oedema was the most common intracranial finding reported.